IMPLEMENTASI APLIKASI E-LEARNING MADRASAH DALAM MENINGKATKAN EFEKTIVITAS DAN HASIL BELAJAR PADA MASA PANDEMI COVID 19 DI MTsN 20 JAKARTA TIMUR - MOHAMMAD SUTARYONO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
The purpose of this writing is to describe how the implementation of the madrasah e-learning application in increasing the effectiveness and learning outcomes at MTsN 20 East Jakarta during the covid 19 pandemic. Data obtained from the results of CBT (PH), PAS and PAT. The results of the analysis were obtained by using the madrasah e-learning application, the quality of students' academic PJJ absorption during PH (CBT), PAS and PAT, the percentage of students participating in Distance Learning was quite optimal, as well as the scores obtained quite satisfactory above KKM 75. In terms of the effectiveness aspect, distance learning using the madrasah e-learning application in terms of the quantity of students participating in CBT (PH) through e-learning reaches 96 - 99% with an average of 84.14, students participating in PAT reach 100%. with an average score of 76, while when students take PAS they reach 96 – 100% with an average score of 80. The conclusion from this writing is that the use of the madrasah e-learning application is considered quite successful in increasing the effectiveness and learning outcomes of students in participating in Distance Learning during the Covid 19 pandemic. ABSTRAKTujuan penulisan ini adalah untuk mendeskripsikan bagaimana implementasi aplikasi e-learning madrasah dalam meningkatkan efektivitas dan hasil belajar di MTsN 20 Jakarta Timur pada masa pandemi covid 19. Data yang diperoleh dari hasil CBT (PH), PAS dan PAT. Hasil analisis didapat dengan menggunakan apliksi e-learning madrasah, kualitas daya serap PJJ akademik siswa pada saat PH (CBT), PAS dan PAT, persentase jumlah siswa yang mengikuti Pembelajaran Jarak Jauh cukup optimal, demikian juga nilai yang diperoleh cukup memuaskan diatas KKM 75. Ditinjau dari aspek efektifitas pengaruhnya, Pembelajaran Jarak Jauh dengan menggunakan aplikasi e-learning madrasah secara kuantitas peserta didik yang mengikuti CBT (PH) melalui e-learning mencapai 96 - 99 % dengan rata-rata 84,14, siswa yang mengikuti PAT mencapai 100% dengan rata-rata nilai 76, sedangkan saat siswa mengikuti PAS mencapai 96 – 100% dengan rata-rata nilai 80. Simpulan dari penulisan ini adalah penggunaan aplikasi e-learning madrasah dinilai cukup berhasil dalam meningkatkan efektivitas dan hasil belajar siswa dalam mengikuti Pembelajaran Jarak Jauh di masa pandemi Covid 19.